2016
DOI: 10.1007/s00508-016-1034-5
|View full text |Cite
|
Sign up to set email alerts
|

Orosomucoid is an independent predictor of prognosis in chronic heart failure

Abstract: Orosomucoid levels are an independent predictor of heart failure-related mortality and hospitalisations in patients with chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38] Transthyretin, hemoglobin subunit alpha, beta, antithrombin III, serum amyloid P-component, fibrinogen α, ß, γ, alpha-1-acid glycoprotein 1 and 2, apolipoprotein A-II, and serotransferrin are relatively highly abundant proteins in human serum and therefore already known biomarkers for cancer, inflammation, cardiac hypertrophy, and heart failure. [28][29][30][31][32][33][34][35][36][39][40][41] Some proteins are known as muscle or cardiac muscle components, such as complement C-4A, C3, obscurin, and titin. 34,35,39,40 We calculated point for screened biomarker candidates with three criteria: First, qualitatively identified number of cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[28][29][30][31][32][33][34][35][36][37][38] Transthyretin, hemoglobin subunit alpha, beta, antithrombin III, serum amyloid P-component, fibrinogen α, ß, γ, alpha-1-acid glycoprotein 1 and 2, apolipoprotein A-II, and serotransferrin are relatively highly abundant proteins in human serum and therefore already known biomarkers for cancer, inflammation, cardiac hypertrophy, and heart failure. [28][29][30][31][32][33][34][35][36][39][40][41] Some proteins are known as muscle or cardiac muscle components, such as complement C-4A, C3, obscurin, and titin. 34,35,39,40 We calculated point for screened biomarker candidates with three criteria: First, qualitatively identified number of cases.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-1-acid glycoprotein 1 is an acute-phase protein with increased expression in inflammatory conditions or cancer. [28][29][30] Clusterin is a serum protein that protects cardiomyocytes and inhibits complement systems. [31][32][33] There are contradictory results about the elevation or decrease in the level of serum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ORM exhibits many biological activities, including modulating immunity, binding and carrying drugs, maintaining the capillary barrier and acting as a disease marker. 17 The role of ORM in cancer, 18 , 19 , 20 cardiovascular diseases 21 , 22 and energy metabolism 23 was revealed recently. We previously reported that ORM was significantly elevated in the sera, liver and muscle tissues of fatigued rodents (for example, sleep-deprivation, forced swimming and treadmill-running models) and the sera of chronic fatigue syndrome patients.…”
Section: Introductionmentioning
confidence: 99%